Tramadol and Paracetamol Fixed Combination in a Portuguese Primary Care Unit: A Cross-Sectional Study - Pedrosa, Bruno; Santos, Catarina; Martins, Marília; Gouveia, Fábio; Franco, Fátima; Vardasca, Margarida; Nogueira, Jorge (Gazeta Médica, 2024)
Introduction: Tramadol/paracetamol combination is one of the most prescribed pain medications in Portugal. At the Regional Health Administration of Lisbon and Tagus Valley, 1 119 229 packages of tramadol/paracetamol were prescribed for 12 months, corresponding to the second most prescribed analgesic. We ask whether this drug is prescribed for acute and irruptive pain or if it is prescribed as a long-term treatment for chronic pain. Methods: This cross-sectional study describes the prescription of tramadol/paracetamol in a Portuguese primary care unit. The population studied corresponds to the 344 patients who received a tramadol/paracetamol prescription between July 2020 and June 2021. Results: In this period, a total of 687 prescriptions were made, corresponding to 2500 packages of tramadol/paracetamol, of which 1874 were bought. There was no statistically significant difference between the number of packages bought over the 4 trimesters (p = 0.275) and 35.3% of the patients bought this medication in more than one trimester. We found that 16.5% bought tramadol/paracetamol in an amount that allows a use of more than 90 days. Conclusion: This demonstrates that the tramadol/paracetamol combination plays a central role in the treatment of pain and that a significant percentage of patients use this medication chronically, questioning the adequacy of this therapy in these patients. However, larger studies that assess pain control are needed to support the results presented in this work.